A study on prevalence of tobacco consumption in tribal district of Madhya Pradesh - Verma, Prashant; Saklecha, Deepak; Kasar, Pradeep Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco use is one of the common risk factors for major non-communicable diseases. It succumbs half of its users to death. Estimates suggest that tobacco will cause about 150 million deaths in the first quarter of the century and 300 million in the second quarter. Prevalence of tobacco use in rural area is higher than urban area. While there is still paucity of data of tobacco consumption among tribal population. The study aims to determine the prevalence of tobacco consumption and its different modes among tribal population. Methods: A cross-sectional study carried out among 800 study subject 15 years and above of randomly selected villages of Mandla district of M.P., from January 2015 to June 2015 using a pre-designed pre-tested proforma. Results: Tobacco consumption was prevalent among 43.38% of the study subjects with khaini (68.3%) being the most common form of tobacco consumed followed by betel nut (9.5%). Its consumption was significantly associated with gender, age group, educational status and the marital status of the respondents. Conclusions: The prevalence of tobacco use is alarmingly high (43.38%). There is a need to strengthen IEC and Behaviour change communication activities focussing on the hazardous effects of tobacco through health education campaigns is needed in tribal areas.